Test-Retest-Reliability of Video-Oculography During Free Visual Exploration in Right-Hemispheric Stroke Patients With Neglect - Kaufmann, Brigitte Charlotte; Cazzoli, Dario; Müri, René Martin; Nef, Tobias; Nyffeler, Thomas (Frontiers in Neuroscience, 2020)
The Mean gaze position during free visual exploration (FVE) is a sensitive tool to detect neglect in patients after a right-hemispheric stroke. Here we investigated the test-retest-reliability of mean gaze position during FVE in 23 patients with left-sided neglect after a first-ever sub-acute right-hemispheric stroke. We analyzed the reliability between different test sets administered within 11 days (test sets A and B, each including different images and their mirrored versions), and between repeated measures using the same test set administered three times within 2 days (test set C, including the same images and their mirrored versions). The intra-class correlation coefficient (ICC) showed good reliability between the two different test sets (test sets A and B; ICC = 0.819), and excellent reliability for the repeated measures with the same test set C (ICC = 0.964). FVE can therefore be recommended for the longitudinal assessments of patients’ neglect severity during neurorehabilitation as well as in treatment trials.